ETHNOMATHEMATICS-PROBLEM BASED LEARNING IN THE “BALOY ADAT TIDUNG” CONTEXT: EFFECTS ON STUDENTS’ MATHEMATICAL CREATIVITY AND GROWTH MINDSET - Sury Adellia Ramadhanta; Marsigit Marsigit (JURNAL EDUSCIENCE, 2026)
Purpose – This study aimed to examine the effectiveness of Ethnomathematics-based Problem-Based Learning (PBL) and Ethnomathematics-based Student Teams Achievement Division (STAD) in enhancing students' Mathematical Creative Thinking Ability (MCTA) and Growth Mindset (GM), and to determine which instructional model is more effectiveMethodology – A quasi-experimental, nonrandomized control-group pretest–posttest design was employed at a public junior secondary school in Indonesia during the 2025/2026 academic year. The sample consisted of two intact ninth-grade classes (32 students each) assigned to the PBL and STAD groups. Data were collected using a mathematical creative thinking test and a growth mindset questionnaire administered at pretest and posttest. Data analysis involved one-sample t-tests to assess the effectiveness of each learning model against the established effectiveness criteria; differences in effectiveness between groups were analyzed using a multivariate test (Hotelling's T²) to see the simultaneous effect on MCTA and GM, independent-samples t-tests to compare group differences, and a superiority analysis to identify the more effective approach.Findings – Both Ethnomathematics-based PBL and STAD were effective in improving students' MCTA and GM. However, the PBL model demonstrated significantly greater effectiveness than the STAD model in enhancing both variables.Contribution – This study provides empirical evidence supporting the integration of the ethnomathematical context "Baloy Adat Tidung" into mathematics instruction. The findings contribute to the literature on culturally responsive pedagogy by demonstrating that ethnomathematics-based PBL is a more impactful approach for strengthening students' creative thinking skills and growth mindset at the junior secondary level.